Analisis Studi Kelayakan Bisnis Butik Baju Muslimah Sha&Sa - Azzahra, Nabila; Ramadhani, Nabila Rizki; Lubis, Nazia Safira; Lubis, Putri Kemala Dewi (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to evaluate the business feasibility of the Muslimah clothing boutique "Roemah Sha & Sa" located in Tanjung Morawa, Deli Serdang. The aspects reviewed in the business feasibility study include legal, environmental, market and marketing, technical and technological, management and human resources, and financial aspects. This research provides an overview of the potential for business success in the Muslim fashion industry. The method used in this research is a qualitative and quantitative approach (mix methods) where the stages are observation, interviews and documentation. The results of the menu analysis show that this business has a significant market opportunity by offering premium Muslim fashion products that comply with sharia. The strategic advantage of "Roemah Sha & Sa" lies in its variety of high-quality products and effective digital marketing strategies. Based on financial calculations, this boutique has stable profit potential with a projected monthly net profit of IDR 11,500,000. These findings suggest that "Roemah Sha & Sa" is worthy of continuation and further development.